Socialization in Sambo and Inter-Generational Transfer of Sambo Value - Blomqvist Mickelsson, Tony (Italian Sociological Review, 2024)
The sport of sambo is the result of the Soviet legacy, embedded in a rich historical tradition that seek to guide its practitioners through life. Here, I explore how this legacy is expressed through its practitioners, specifically, post-socialist sambo-practicing migrants. I conceptualize sambo’s imprint as a structural and cultural conditioner according to Archer’s (1995) analytical dualism, predisposing them towards certain situational logics. When the sambo practitioners interact with local sport environments, several courses of action are discerned. For the first-generation migrants who are born into the ‘sambo way’, the influence of sambo weighs heavily in their decision-making. This is negotiated, and the agency plays a vital part when integrating into the mainstream sports-sphere. However, for migrants not born into the sambo doctrine, the influence is peripheral and diminished in favor of other, stronger, belief systems. In conclusion, sambo exerts a strong normative force, but the transmission between generations severely hampers the meaning and impact of sambo.